Selfies And Cultural Events: Mixed Methodologies For The Study Of Selfies In Context - San Cornelio, Gemma; Roig, Antoni; Ardèvo, Elisenda; Enguix, Begonya (AoIR Selected Papers of Internet Research, 2017)
Mass events, such as concerts, music festivals, conventions about technology and popular culture are privileged spaces to showcase the exceptionality of a lived experience. And in these contexts the selfie can be considered one of the better ways of expression of the ‘here’ and the ‘now’, as well as a key element when integrated in the everyday personal narratives favoured by social media platforms like Instagram. Thus, the analysis of selfies in the context of cultural events is part of the ongoing research project “Selfie stories and personal data”, (www.selfiestories.net) funded by the BBVA Foundation (2015-2017), in which the present paper is framed. In selfiestories we address the phenomenon of the selfie as part of a personal or a collective narrative (Vivien and Burgess, 2013) in social media sites. Our methodological approach involves a hybrid perspective or ‘mixed method’ (Markham, 2013). On the one side, we conduct ethnographic fieldwork in order to get a better understanding of different forms of personal narratives and, on the other side, we took a Big Data approach. We have obtained the data with our own data extractor, a scraper based on the Instagram API, which has been used for different case studies. Specifically, in this paper we will present some of the results obtained from two events occurred in Barcelona in 2016: the music festival Primavera Sound and the Barcelona Games World convention. Looking into selfies through this perspective allows to compare the performances of fieldwork with Instagram data analysis.